A1.3 Safe paediatric anaesthesia project: scaling-up paediatric anaesthesia training in east and central africa. (4th October 2017) - Sharkey, E; Boyd, N; Burton, Z; Tumukunde, J; Nabukenya, M; Sipuka, N; Zyambo, M; Nabulindo, S; Rodney, G; Mndolo, S; Gemechu, TB; Bould, D; et al.
Abstract : Background: The burden of treatable surgical diseases in children in low- and middle-income countries (LMICs) is greater than that of malaria, HIV/AIDS and TB combined. World Health Organisation member states are required to scale up access to emergency and essential surgery for children by 2030 as part of universal health coverage. There is a critical shortage of anaesthetists trained to look after children in LMICs. The aim of this project was to deliver the Safer Anaesthesia From Education (SAFE) Paediatric course in East and Central Africa, and to evaluate the impact of this training programme. Methods: The SAFE Paediatric anaesthesia course is a three-day short course developed by GOSH paediatric anaesthetists in collaboration with the Association of Anaesthetists of Great Britain and Ireland (AAGBI), World Federation of Societies of Anaesthesiologists (WFSA) and Association of Anaesthesiologists of Uganda (AAU). It focuses on common paediatric surgical conditions encountered in LMICs. A one-day Train-The-Trainer (TTT) course was also established to train future SAFE faculty. Results: A total of nine SAFE courses were delivered. 'SAFE fellows' conducted follow-up interviews in Uganda, Zambia and Malawi. 46/57 (81%) faculty members who completed the TTT course taught on a subsequent SAFE course. 381 delegates completed the course. Mean MCQ scores increased from 37.6/50 pre-course to 43.4/50 post-course and skills scores increased from 5.8/10 to 8/10 (p<0.001). Follow-up showed significantly higher mean MCQ (pre-course 37.6/50, follow-up 41.5/50) and skills test scores (pre-course(5.8/10), follow-up(8.2/10)). All interviewed delegates reported increased confidence in providing paediatric anaesthesia. Conclusion: The SAFE paediatric anaesthesia course provides high quality education for anaesthetists in LMICs. Knowledge and skills improve and are retained at follow-up. SAFE course training results in changes in paediatric anaesthesia practice and improved patient outcomes. Delivery of the SAFE training through UK/LMIC anaesthesia health partnerships builds links between paediatric anaesthetists internationally.